PENGARUH RETAIL MARKETING MIX TERHADAP LOYALITAS KONSUMEN DENGAN KEPUASAN KONSUMEN SEBAGAI PEMODERASI - Alfa Santoso Budiwidjojo Putra (Jurnal Riset Manajemen dan Bisnis, 2012)
The study aimed to analyze the effect of the retail marketing mix toward customer loyalty withcustomer satisfaction as a moderating variable on the minimarket Alfamart in Yogyakarta.The data was analysed base on moderated regression analysis. The results showed that fourof the six elements of the retail marketing mix, i.e. pricing, retail service, promotion and storeatmosphere significantly influence customer loyalty. Second, a significant influence oncustomer satisfaction as a moderating variable in strengthening the interaction occurs onlybetween pricing on customer loyalty.Keywords: retail marketing mix, satisfaction, loyalty